Different vertical heat transport induced by submesoscale motions in the shelf and open sea of the northwestern South China Sea - Pan, Hao; Qiu, Chunhua; Liang, Hong; Zou, Liwei; Zhang, Ziqi; He, Benjun (Frontiers in Marine Science, 2023)
Submesoscale currents are known to be associated with strong vertical velocities (O (10) m/day), regulating the redistributions of energy and matter balances. The northern South China Sea (SCS) is fulfilled with submesoscale motions, which might induce strong vertical heat transport (VHT). We set up a 1-km horizontal resolution Massachusetts Institute of Technology General Circulation Model (MITgcm) to study the seasonal variations in submesoscale vertical heat transport in shelf regions and open seas. Spectrum analysis shows that the spatial scale separating submesoscale and mesoscale motions are 14 and 30 km for the shelf and open regions, respectively. The submesoscale VHT in the shelf region is one order of magnitude larger than that in the open ocean. The former has the largest value in summer and winter, which might be induced by summer upwelling and winter downwelling, while the latter is strongest in winter and weakest in summer in open regions. The submesoscale VHT also appears to have intra-seasonal variations and might be attributed to the disturbances of tropical cyclones and life stages of submesoscale eddies. The submesoscale VHT is strongest in the pregeneration phase of the eddies, and the maximum VHT belt has an entrainment type at the developing and mature stages. The chlorophyll-a concentration also has the same temporal variation as the different life-stage of eddies. This study provides local VHT induced by submesoscale motions, which is expected to improve our understanding of submesoscale air–sea interactions and their biological effects.